ANALYSIS OF SUPPLY CHAIN MANAGEMENT IN AN ATTEMPT TO ESCALATE BLACK TEA PRODUCTION AT PT PERKEBUNAN TAMBI WONOSOBO, CENTRAL JAVA - Khusna, Alvina Ziadatul; Mashudi, Mashudi (PT. Antis International Publisher, 2024)
Objective: This study aims to analyze the role of supply chain management (SCM) in addressing production constraints and increasing black tea production at PT Perkebunan Tambi, where demand exceeds supply, causing operational inefficiencies. Methods: A descriptive qualitative approach was employed, involving systematic observations, documentation, and interviews with key informants from the production and marketing divisions. This approach enabled a detailed analysis of phenomena affecting supply chain activities and production processes. Results: The findings indicate that the implementation of SCM at PT Perkebunan Tambi is suboptimal due to recurring constraints in key areas, including machinery reliability, transportation of tea shoots, workforce readiness, and inventory management. The primary bottleneck lies in the aging machinery, which, despite regular maintenance, fails to perform effectively, leading to production delays and reduced output. These challenges hinder the alignment of production capacity with market demand, creating a supply-demand gap. Novelty: This study highlights the critical link between aging infrastructure and supply chain inefficiencies, emphasizing the need for strategic machine renewal and improved inventory management to sustain continuous operations and meet growing market demands. The research provides actionable insights into overcoming production challenges through enhanced SCM practices, contributing to the literature on supply chain optimization in tea production industries.